USING DUBBING AND SUBTITLING METHODS THROUGH FILM IN MOTIVATING STUDENTS IN ENGLISH SPEAKING AND CONVERSATION - Fitria, Tira Nur (Jurusan Sastra Indonesia, 2023)
This research describes the use of the dubbing and subtitling method through film in motivating students in English speaking/conversation. This research is library research. The analysis shows that the video project of dubbing in the film is engaging, motivating, and effective in improving language abilities. However, film media using dubbing can be combined with subtitling methods to make English learning more interesting, imaginative, and engaging. It means that both dubbing and subtitling can be used to practice English conversation skills with film. They can be applied to motivate students and even improve pronunciation and vocabulary mastery. Dubbing involves imitating the actors’ voices and acting out dialogue scenes to practice students' pronunciation. Subtitling involves the use of Indonesian language transcription (Indonesian subtitling version) and English transcription (English subtitling version) for helping students to understand the vocabulary meaning in the dialogue. To motivate students’ English speaking/conversation skills with those methods, students can choose their favorite films and actors, choose short film materials and search for subtitles, and practice English speaking in monologs or conversations in pairs. So, students can be interested and motivated, even improving their overall language learning experience. The previous studies also indicate the use of the dubbing/subtitling method in film improves students' motivation and enthusiasm in English speaking/conversation.